Nanotechnology for fabrication of nanoparticles and nanoemulsion - Mohamed, Farahidah; Mohd Nor, Nurul Hafizah; Budipatama, Anugerah; Mohd Shafri, Mohd Affendi (2017)
Therapeutic agents, namely drugs (i.e. Active pharmaceutical ingredient, API), biopharmaceutical (e.g. protein/peptide/macromolecules) and natural products (e.g. Nigella sativa oil, alpha mangostin) may have drawback of either highly water-soluble or highly lipophilic. These two extreme properties can mask the actual efficacy of the agents regardless of route of administration due to poor absorption across biological membrane. Nanotechnology appear to provide potential solution to these problems. Here, we had attempted a fabrication of nanoparticles and nanoemulsion for DNA-Nigella sativa oil and Doxycycline-Nigella sativa, respectively. For the nanoparticles, DNA-Nigella sativa was encapsulated into biodegradable poly(lactide-coglycolide) (PLGA: glycolic acid to lactic acid ratio of 50:50; IV 0.1 dl/g) polymer with or without chitosan and with or without sorbitan surfactant, using emulsion-solvent evaporation technique. The chitosan molecular weight (MW) was also varied. The DNA-Nigella sativa (DNN) nanoparticles were characterized for particle size using dynamic light scattering, Nanosizer and zeta potential using a Zetasizer. The results revealed particles of size ~870 to 134 nm showing large variation when immersed in deionized water as compared to alkaline media. Zeta-potential showed negative values for non-chitosan particles and positive values for all chitosan-containing particles. Microimages from Field emission Scanning Electron Microscopy (FESEM) revealed DNN nanoparticles of less than 300 nm. For the nanoemulsion, 3 phases were separately prepared, namely doxycycline/preservatives as the aqueous phase, nigella sativa oil/eugenol as the oil phase and lecithin/surfactant as the nanoemulsifier phase. The three phases were added and homogenized at 3000 rpm using a vacuum homogeneous mixer. This method yielded about 300 nm nanoemulsion droplets, PDI of 0.4 and zeta potential of -69. Further rheological characterization revealed that the nanoemulsion had thixotropic property suitable for its intended use as local antibiotic injected into periodontal gum pocket. In conclusion, with appropriate fabrication method, nanotechnology can be potentially explored to mitigate inherent problems of highly lipophilic or hydrophilic therapeutic agents hence unmask actual efficacy of these agents.